Life Cycle Assessment of Sago Palm, Oil Palm, and Paddy Cultivated on Peat Land - Saptarining Wulan; Haryoto Kusnoputranto; Jatna Supriatna; H.M.H. Bintoro Djoefrie; Hisyam Musthafa Al Hakim (Center for Journal Management and Publication, 2015)
The continuously increasing population growth more than food agriculture growth on the existing land, has been encouraging to this research. The land use competition for agriculture and housing purposes have caused the land use change from forest to agriculture and housing. Within forested landscapes food production, commodity agriculture, biodiversity, resource extraction and other land uses are also competing for space. The forest land use change (deforestation) is one of the climate change causes. The impact of climate change among others is the uncertain climate, such as the long drought period, flood, and the extreme temperature that cause decreasing in agriculture production. Therefore, at present, many people use the marginal land, such as peat land for agriculture cultivation to increase the food agriculture production and to achieve the domestic and export demand. Indonesia has a huge peat land and the fourth biggest in the world after Rusia, Canada, and America. The focus of this study is comparing the life cycle assessment of three agriculture commodities: sago palm, oil palm, and paddy cultivated on peat land. The purpose of this research is to contribute a recommendation of the most sustainable commodity from the aspect carbon dioxide (CO2) emission among three food agriculture commodities include oil palm and paddy that currently as excellent commodities, and sago palm, the neglected indigenous plant, which are cultivated on peat land. The method applied for this research to analyze the environmental aspect using life cycle assessment (LCA) started from seedling, plantation, harvesting, transportation, and production process. The analysis result reveals that sago palm is the most environmental friendly. The lowest CO2 emission (ton/ha/year) is sago palm (214.75 ± 23.49 kg CO2 eq), then paddy (322.03 ± 7.57 kg CO2 eq) and the highest CO2 emission (ton/ha/year) is oil palm (406.88 ± 97.09 kg CO2 eq).